Sjukdomsfrekvens och utslagningsorsaker hos kor med 12 respektive 15 månaders kalvningsintervall - Edvardsson, Anna (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
The incidence of many of the most common diseases in dairy cattle has been proven to be highest during the time closest to calving. It is possible that the current breeding strategy with 12 month calving intervals increases the risk for disease in dairy cattle, which is problematic concerning both animal welfare and for economic reasons. The economic incentives behind a calving interval of 12 to 13 months have mainly been based on milk- and feed- costs and no costs due to diseases or fertility disturbances have been included.